Distribution of spontaneous plant hybrids. - Ellstrand, N C (1996)
Natural hybridization is a relatively common feature of vascular plant species and has been demonstrated to have played an important role in their evolution. Nonetheless, it is not clear whether spontaneous hybridization occurs as a general feature of all plant families and genera or whether certain groups are especially prone to spontaneous hybridization. Therefore, we inspected five modern biosystematic floras to survey the frequency and taxonomic distribution of spontaneous hybrids. We found spontaneous hybridization to be nonrandomly distributed among taxa, concentrated in certain families and certain genera, often at a frequency out of proportion to the size of the family or genus. Most of these groups were primarily outcrossing perennials with reproductive modes that stabilized hybridity such as agamospermy, vegetative spread, or permanent odd polyploidy. These data suggest that certain phylogenetic groups are biologically predisposed for the formation and maintenance of hybrids.